Family support policies and child outcomes: a realist-scoping review*. Issue 3 (27th May 2017) - Ng, Edwin; Julià, Mireia; Muntaner, Carles; O'Campo, Patricia
ABSTRACT: Family support policies (FSP) refer to government policies that promote the well-being of families with children (e.g. job-protected paid leave, cash transfers, childcare). We developed an initial conceptual and theoretical framework of FSP and conducted a realist-scoping review to document the state of evidence regarding the influence of FSP on three child outcomes: poverty, development, and health. Based on the contexts and mechanisms through which FSP are hypothesized to affect child outcomes, we constructed a framework to guide a search of five electronic databases ( OVID, ProQuest, PubMed, Scopus, and Web of Knowledge ). We analysed articles meeting our inclusion criteria (i.e. conceptualized FSP as a function of the welfare state; conceptualized child poverty, development, and health as outcomes; and conducted empirical analyses) in relation to our mechanisms and thematic concerns (context, developmental periods, and differential impacts). A total of 22 studies met our inclusion criteria, which tested 25 independent child outcomes. Our findings identified initial mechanisms that explain the relationship between FSP and child outcomes through (1) increasing parents' basic capabilities, (2) shaping parents' childcare options, and (3) influencing parental leave-taking and shifting beliefs about gender relationships in the home and workplace. Future work will be to test these mechanisms and framework through a realist synthesis.